Refleksi atas Pemikiran Poskolonial Frantz Fanon dalam Konteks Hegemoni Tanah di Indonesia dan Praksis Sosial Gereja - Tonta, Rex Firenze (STFT Jakarta, Indonesia, 2024)
This study discusses land hegemony in Indonesia, a historical product of colonialism. It is rooted in agrarian policy, which created the term domein verklaring, where land, where proof of ownership cannot be shown, is claimed as state-owned land. This colonial logic continued to be inherited and persisted in land issues even when Indonesia became independent. This paper uses Frantz Fanon's postcolonial theory as an analytical instrument to see the relationship between land hegemony and colonial residue. It is also hoped that the use of Fanon's postcolonial theory can provide an important contribution to the church in the